Management of Admission of New Learners Zoning System to Equalize the Quality of Educational Services to Learners - Eva Nurhasanah; Didin Wahidin; Teti Ratnawulan; Hanafiah Hanafiah (Syntax Corporation Indonesia, 2021)
The gap in the quantity and quality of education between regions, discrimination, and injustice in access and education services is exacerbated by the dichotomy of only and non-superior schools widening the gap in the quality of education in Indonesia. To increase the distribution of quality and equitable quality education services to students, a zoning system PPDB management is needed. On that basis, this study aims to describe the PPDB management of the zoning system to equalize the quality of education services for students at the Tasikmalaya Regency State Senior High School, which includes planning, organizing, preparing personnel, implementing, coordinating, reporting, and budgeting. This research uses a qualitative approach with the type of case study. The research location is SMA Negeri 1 Ciawi, SMA Negeri 1 Karangnunggal and SMA Negeri 1 Cikalong, Tasikmalaya Regency. This study resulted in that: 1) Planning for the zoning system PPDB includes setting goals, formulating current conditions, identifying facilities and obstacles, and developing a series of activities. 2) Organizing the zoning system PPDB includes preparing the organizational structure, dividing workloads, and determining the lines of coordination and authority. 3) Preparation of PPDB personnel for the zoning system includes needs analysis, recruitment of committees according to the main tasks and functions, and training of organizing committees to work according to their duties and functions. 4) Implementation includes PPDB registration, data verification, and selection of prospective students, meeting to determine PPDB selection results, the announcement of PPDB results, and re-registration. 5) Coordination includes coordination with internal schools and coordination with external schools. 6) Reporting includes reports on recapitulation of re-registration received and re-registration, class division, submission of student files to BP/BK and student affairs, evaluation, and preparation of reports. 7) Budgeting includes budget planning and realization of budget use. 8) Obstacles can be seen from technical and non-technical constraints. 9) Solutions and improvement efforts can be seen from technical solutions and non-technical solutions.